High performance THz patch antenna using photonic band gap and defected ground structure. Issue 15 (13th October 2019) - Ullah, Shahid; Ruan, Cunjun; Haq, Tanveer Ul; Zhang, Xingyun
ABSTRACT: In this work, a high-performance THz microstrip patch antenna is designed using defected ground structure and photonic band-gap. The operating frequency of the proposed antenna is 0.690 THz. DGS and PBG are used to enhance gain, directivity, return loss and VSWR of the antenna. The proposed antenna is simulated in two different design software's (CST2015, HFSS2018). First, a rectangular microstrip patch antenna is designed, at 0.696 THz, than RSRR structures are used in the substrate as a PBG. Next, the same RSRR structures are used in the ground known as DGS which enhances the VSWR and return loss of the antenna. The last step decreases the size of the substrate to enhance the value of VSWR up to 1.0015 which is close to unity and return loss, gain and directivity are −64.16 dBi, 6.793 dBi, and 6.914 dBi respectively. The bandwidth of the antenna is 26.7 GHz.